Concerted action of the PHD, chromo and motor domains regulates the human chromatin remodelling ATPase CHD4 - Morra, R; Lee, B; Shaw, H; Tuma, R; Mancini, E (2012)
CHD4, the core subunit of the Nucleosome Remodelling and Deacetylase (NuRD) complex, is a chromatin remodelling ATPase that, in addition to a helicase domain, harbors tandem plant homeo finger and chromo domains. By using a panel of domain constructs we dissect their roles and demonstrate that DNA binding, histone binding and ATPase activities are allosterically regulated. Molecular shape reconstruction from small-angle X-ray scattering reveals extensive domain-domain interactions, which provide a structural explanation for the regulation of CHD4 activities by intramolecular domain communication. Our results demonstrate functional interdependency between domains within a chromatin remodeller. Crown Copyright © 2012 Published by Elsevier B.V. on behalf of Federation of European Biochemical society. All rights reserved.